THE INFLUENCE OF DIVIDEND POLICY, DEBT POLICY, INDEPENDENT COMMISSIONER, AND INSTITUTIONAL OWNERSHIP ON THE FIRM VALUE WITH GROWTH OPPORTUNITIES AS MODERATOR VARIABLES (Study on Non-Financial Companies Listed on IDX in the Period of Years of 2012-2015) - Setiyawati, Lia; Wahyudi, Sugeng; Mawardi, Wisnu (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2017)
Tobin's q is the ratio of market value of equity plus the market value of debt to total assets. This ratio measures the value provided by financial markets for any management and organization as a growing company. Tobin's q also shows how far a company is able to create its value relative to the amount of capital invested. The greater the value of Tobin's q indicates that the company has good growth prospect. This study aimed at examining the influence of Dividend Payout Ratio (DER), Independent Commissioner (KI) and Institutional Ownership (INST) on Tobin's q with Size and Return on Investment (ROI) as control variable and Market to Book Value (MBV) as a moderating variable.The population in this study is all manufacturing companies listed on Indonesia Stock Exchange in the period of 2012-2015. The sampling technique used purposive sampling and obtained 28 companies becoming the research sample. The analysis technique used in this research was multiple regression analysis using SPSS where the data, previously, had been tested using classical assumption tests like normality, multicollinearity, and autocorrelation tests.